2004
DOI: 10.1097/00001756-200411150-00026
|View full text |Cite
|
Sign up to set email alerts
|

Gender related differences on the EEG during a simulated mobile phone signal

Abstract: The present study investigated the gender-related influence of electromagnetic fields (EMF), similar to that emitted by mobile phones, on brain activity. Ten women and nine men performed a short memory task (Wechsler test), both without (baseline) and with exposure to a 900 MHz signal. The EEG energy of the total waveform and the alpha, beta, delta and theta; rhythms were calculated from the recordings of 15 scalp electrodes. Baseline EEG energy of males was greater than that of females, while exposure to EMF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
3
21
0
1
Order By: Relevance
“…This variable may also interact with the sex of the subject, as there are known differences in laterality between males and females. Two studies within this review [Smythe and Costall, 2003;Papageorgiou et al, 2004] found that sex interacted significantly with EMF exposure in both performance and EEG measures. Whether these observations are related to true sex differences remains to be verified.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This variable may also interact with the sex of the subject, as there are known differences in laterality between males and females. Two studies within this review [Smythe and Costall, 2003;Papageorgiou et al, 2004] found that sex interacted significantly with EMF exposure in both performance and EEG measures. Whether these observations are related to true sex differences remains to be verified.…”
Section: Discussionmentioning
confidence: 87%
“…This observation, although not universally reported, is noted over several electrophysiological studies [Huber et al, 2002[Huber et al, , 2003[Huber et al, , 2005Hamblin et al, 2004;Hinrichs and Heinze, 2004;Curcio et al, 2005]. Immediate effects of mobile phone exposure were seen in several studies [Croft et al, 2002;D'Costa et al, 2003;Krause et al, 2004;Papageorgiou et al, 2004]. Interestingly, no EEG or ERP studies reported null effects.…”
Section: Elf-modulated Radiofrequency Exposure Studies Involving Elecmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the study by Hietanen et al [2000] did not satisfy criteria (c) and (d). Furthermore, Papageorgiou et al [2004] failed to meet criteria (a), (c) and (d) whereas in their subsequent study [Papageorgiou et al, 2006] criteria (a) and (c) were not satisfied. Two studies did not satisfy any of the inclusive criteria [Kramarenko and Tan, 2003;Monnery et al, 2004].…”
Section: Literature Search and Selectionmentioning
confidence: 91%
“…Russo et al reported no statistically significant differences between performances under CW versus PM exposure. Electroencephalogram (EEG) studies, on the other hand, have exposed either the left [Kramarenko and Tan, 2003;Krause et al, 2004], the right [Krause et al, 2000a,b;Papageorgiou et al, 2004], or both hemispheres [Reiser et al, 1995;Mann and Röschke, 1996;Röschke and Mann, 1997] to EMF, thus raising the question of possible differences in the EMF effects under left or right hemispheric exposure. All in all, there is a considerable variation in the results of the quoted studies.…”
Section: Introductionmentioning
confidence: 99%